2016
DOI: 10.5194/hess-20-1331-2016
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate change under CMIP5 RCP scenarios on the streamflow in the Dinder River and ecosystem habitats in Dinder National Park, Sudan

Abstract: Abstract. The fate of seasonal river ecosystem habitats under climate change essentially depends on the changes in annual recharge of the river, which are related to alterations in precipitation and evaporation over the river basin. Therefore, the change in climate conditions is expected to significantly affect hydrological and ecological components, particularly in fragmented ecosystems. This study aims to assess the impacts of climate change on the streamflow in the Dinder River basin (DRB) and to infer its … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 43 publications
4
43
0
Order By: Relevance
“…The three RCPs use radiative forcing values of 2.6, 4.5 and 8.5 W/m −2 , respectively [28]. Different temporal scale outputs (daily or monthly) of GCMs have been used by various studies to assess climate change effects on hydrology [29][30][31][32]. However, some studies pointed out that the daily outputs of GCM could not be directly used [15] and monthly GCMs outputs were widely used in the northwest China [33,34].…”
Section: Global Climate Model Datamentioning
confidence: 99%
“…The three RCPs use radiative forcing values of 2.6, 4.5 and 8.5 W/m −2 , respectively [28]. Different temporal scale outputs (daily or monthly) of GCMs have been used by various studies to assess climate change effects on hydrology [29][30][31][32]. However, some studies pointed out that the daily outputs of GCM could not be directly used [15] and monthly GCMs outputs were widely used in the northwest China [33,34].…”
Section: Global Climate Model Datamentioning
confidence: 99%
“…In this study, the Linear Scale Factor (LSF) approach [29][30][31][32] under the statistical downscaling method was used. This method has been used for many basins [27].…”
Section: Representative Concentration Pathways Scenario Data and Biasmentioning
confidence: 99%
“…Field-and watershed-scale models have been used to evaluate nutrient reduction strategies, and it is important to accurately simulate hydrological processes of tile drainage systems for evaluation of hydrological and water quality impacts of conservation practices in watersheds in the Midwest (Guo et al, 2018). The Soil and Water Assessment Tool (SWAT), a physically based and watershed-scale hydrological model, has been widely used to simulate land use change impacts on water quantity and quality (Basheer et al, 2016;Guo et al, 2015;Luo et al, 2012;Shope et al, 2014;Teshager et al, 2016;Wang et al, 2016;Yin et al, 2016), but studies on simulation of tile drainage impact at field and watershed scales using the new tile drainage routine from SWAT2012 are few (Boles et al, 2015;Du et al, 2005Du et al, , 2006Moriasi et al, 2005Moriasi et al, , 2012. For instance, Sui and Frankenberger (2008) quantified the impact of tile drains on nitrate loss in an extensively tiledrained watershed, and showed that simulated nitrate loss results by SWAT2005 could be used for simulation of nitrate reductions at the watershed scale.…”
Section: Introductionmentioning
confidence: 99%